2013
DOI: 10.1371/journal.pone.0076446
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Cell Death – Antiapoptotic Bcl-2 Proteins Regulate Migration and Invasion of Colorectal Cancer Cells In Vitro

Abstract: Migration and invasion of malignant cells are prerequisites for cancer progression and metastasis. The Bcl-2 family of proteins consists of about 25 members and has been extensively studied in the context of apoptosis. Despite the fact that small molecules targeting Bcl-2 proteins have already entered clinical trials, very few studies investigated a role of antiapoptotic Bcl-2 proteins beside cell death in the context of metastasis. The aim of this study was to dissect a potential role of the antiapoptotic Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 46 publications
(56 reference statements)
5
91
0
2
Order By: Relevance
“…This unique function, which goes beyond the antiapoptotic activity of full-length MCL-1 protein, makes MCL-1 indispensable for the survival of cancer cells (26,40). Furthermore, MCL-1 reportedly enhances the migratory and invasive potential of colorectal tumor cells, independently from its antiapoptotic effects (25,31). Consistently, we observed that improved ATP production, as well as enhanced migration and invasion of PHD3-deficient tumor cells, could be reverted by simultaneous knockdown of MCL-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique function, which goes beyond the antiapoptotic activity of full-length MCL-1 protein, makes MCL-1 indispensable for the survival of cancer cells (26,40). Furthermore, MCL-1 reportedly enhances the migratory and invasive potential of colorectal tumor cells, independently from its antiapoptotic effects (25,31). Consistently, we observed that improved ATP production, as well as enhanced migration and invasion of PHD3-deficient tumor cells, could be reverted by simultaneous knockdown of MCL-1.…”
Section: Discussionmentioning
confidence: 99%
“…Among other molecules (and HIF in particular, see below), we focused on MCL-1, a BCL-2 family member, which is expressed in colorectal cancer (24,25). MCL-1 protein undergoes proteolytic cleavage.…”
Section: Phd3 Expression Affects Mitochondrial Atp Production Of Tumomentioning
confidence: 99%
“…A recent report suggested that the prosurvival Bcl2 protein modulates autophagy only indirectly, by inhibiting the apoptosis mediators Bax and Bak [103] . Bcl2 has been associated with migration and invasion of malignant cells and with the prevention of apoptosis in pT3 CRC patients [104,105] . In addition, the overexpression of Bcl2 in CRC was correlated with resistance to paclitaxel [106] .…”
Section: Bcl2 Genementioning
confidence: 99%
“…Among anti-apoptotic genes, expression of survivin and Bcl-2 genes contributes to determine the resistance of a majority of colon tumor cells to chemotherapy, tumorigenesis and poor prognosis [7,8]. Expression of survivin and Bcl-2 has been shown to be up-regulated in colorectal cancer [7,9]. These genes are overexpressed in the most human cancers but rarely in normal tissues [7,8].…”
Section: Introductionmentioning
confidence: 99%